Nutritional condition of wild and hatchery‐reared, green‐lipped mussel (Perna canaliculus) spat used for aquaculture - Bradley M. Skelton; María Múgica; Leonardo N. Zamora; Natalí J. Delorme; Jenni A. Stanley; Andrew G. Jeffs (Aquaculture, Fish and Fisheries, 2024)
Abstract The nutritional condition of seed mussels (spat) at the time of seeding is thought to play a major role in influencing spat losses on mussel farms, with nutritionally compromised spat thought to be more likely to be lost from aquaculture substrata than those in good condition. New Zealand's Greenshell™ mussel (Perna canaliculus) aquaculture industry relies almost exclusively (∼85%) on wild caught spat, with the vast majority, typically > 90%, lost shortly after being seeded onto coastal mussel farms. This study sought to quantify the extent of the variability in the nutritional condition (i.e., calorific, protein, lipid and carbohydrate content) of samples of spat used by the Greenshell™ industry between 2014 and 2021 (i.e., wild caught and hatchery produced) as a first step towards determining whether variability in nutritional condition may be a significant contributor to the marked variation observed in spat performance after it is seeded onto coastal farms. All parameters measured were highly variable among wild spat samples, with all but lipid content varying, including for samples of wild spat harvested at different times within the same month. Furthermore, there were no clear patterns in the nutritional condition of spat across months or years, suggesting environmental factors that limit feeding during the harvest and transport of spat may be contributing to marked differences in the quality of spat being used by the industry to seed farms. These results provide a baseline for assessing the nutritional condition of Greenshell™ spat and point towards a need to develop interventions to improve the quality of wild spat supply for this industry to help and prevent the ongoing massive losses of spat from farms. These measures could include, testing nutritional condition of spat at harvest or prior to seeding, development of nursery culture methods and development of artificial spat feeds that have the potential to replace live phytoplankton during nursery culture.